2018
DOI: 10.1016/j.amjms.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Major Depressive Disorder and Outcomes in Older Veterans Hospitalized With Pneumonia

Abstract: For older veterans hospitalized with pneumonia, a concurrent diagnosis of major depressive disorder, and especially untreated depression, was associated with higher mortality. This highlights that untreated major depressive disorder is an independent risk factor for mortality for patients with pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In contrast, the risk of suicide in other types of mental disorders was 12.7% in total [ 4 ]. The overall incidence of depression in the elderly in China was 23.6% [ 5 ], and depression was an independent risk factor for death due to various complications (such as heart failure, cancer, and stroke) [ 6 ]. Therefore, it is especially vital to further investigate the relevant targets and mechanisms during the development of depression.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the risk of suicide in other types of mental disorders was 12.7% in total [ 4 ]. The overall incidence of depression in the elderly in China was 23.6% [ 5 ], and depression was an independent risk factor for death due to various complications (such as heart failure, cancer, and stroke) [ 6 ]. Therefore, it is especially vital to further investigate the relevant targets and mechanisms during the development of depression.…”
Section: Introductionmentioning
confidence: 99%
“… 6 A previous study with a large cohort (n=103 997) showed that chronic mental illness is an independent risk factor for mortality in patients with pneumonia. 15 In addition, infectious pathogens (eg, toxoplasma, cytomegalovirus, Epstein-Barr virus) chronically induce or aggravate mental illness, including psychiatric disorders, cognitive disorders, personality disorders, and suicidal behaviour. 16 These findings imply that mental illness is inherently associated with worse clinical pathophysiology rather than just affecting health screening or transmission of infection.…”
Section: Discussionmentioning
confidence: 99%
“…6 A previous study with a large cohort (n=103 997) showed that chronic mental illness is an independent risk factor for mortality in patients with pneumonia. 15 In addition, infectious patho gens (eg, toxoplasma,…”
Section: Discussionmentioning
confidence: 99%
“…Major depressive disorder (MDD) is a common mental disorder and is associated with a higher risk for many comorbid conditions, such as heart failure, cancer and stroke [1]. Metabolic syndrome (MetS) is a cluster of cardio-metabolic risk factors and comorbidities conveying high risk of both cardiovascular events and cerebrovascular disease [2].…”
Section: Introductionmentioning
confidence: 99%